PATHOMORPHOLOGY OF BREAST CANCER (Journal of Universal Science Research, 2024)
According to the World Health Organization (WHO), in 2022, around 670,000 women died from breast cancer worldwide. Just alone in the USA, an estimated 43,170 women passed away due to breast cancer in 2023. There is a 1 in eight chance that women will get breast cancer in their lives. Breast cancer is the fifth leading cause of death for women all over the world.It is important to understand a little bit about Breast cancer, In simple words a cancer is abnormal growth or uncontrolled cell growth which typically leads to the formation of a tumor Now these tumors can be classified into benign or malignant to make it simple benign are localized and do not spread or they are Non-metastatic (they don't spread to other area or organ of the body) meanwhile malignant are opposite of benign they are not localized they are metastatic they can spread to other area of the body Breast cancer can be either benign or malignant.